Association of SMAD3 Gene rs12901499 Variation with Knee Osteoarthritis in Indonesian Aged Women - Zaki, Achmad; Adhiyanto, Chris; Hendarmin, Laifa Annisa; Naqiya, Fauzia Ilman; Karni, Dwi; Harriyati, Zeti (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Small Mother Against Decapentaplegic 3 (SMAD3), an intracellular transducer protein in the TGF-β signaling pathway, has a role in maintaining joint cartilage. Many studies have been conducted to examine the effect of polymorphism in SMAD3 gene with the incidence of osteoarthritis (OA). The objective of this study is to identify the association of SMAD3 gene rs12901499 variation with the incidence of knee OA in Indonesian women. We conducted an analytic cross-sectional design involving 24 knee OA patients and 50 non-OA subjects. The DNA was taken from saliva and genotyped using a kit from Integrated DNA Technologies with the Real Time PCR method. In this study, we found that the GA genotype (heterozygous mutant) of the rs12901499 allele was the allele that most frequently (50%) appeared in knee OA patients as well as non-OA subjects (50%). The G allele frequency was higher than the A allele among all participants. The Chi-Square analysis showed that there was no statistically significant relationship between allele variations in the SMAD3 rs12901499 gene and knee OA (p=1). In conclusion, there was no statistically significant relationship between the rs12901499 genetic variation in the SMAD3 gene and the incidence of knee osteoarthritis in Indonesian aged women.